Managing airports an international perspective - Graham, Anne, 1958- (Butterworth-Heinemann, 2008)
Managing Airports presents a comprehensive and cutting-edge insight into today's international airport industry. Approaching management topics from a strategic and commercial perspective rather than from an operational and technical angle, the book provides an innovative insight into the processes behind running a successful airport. Completely revised and updated for a third edition, with international case studies from BAA, Vienna, Aer Rianta, and countries around the world, this book reflects the huge changes in the management of airports today and tackles many key issues. Accessible and up-to-date, Managing Airports is ideal for students, lecturers and researchers of transport and tourism, and practitioners within the air transport industry. . Vast increases of air traffic - how can airport development cope with predicted levels of future demand? . Commercialization and privatization of airports and the emergence of new types of airport operators as the private airport industry has matured. . The increased number of airline alliances and the new demands they place on the airport operators. . The growth of the low cost carrier sector and its impact on airport operations worldwide. . Security and the environmental impacts.
Previous edition: 2003.
Keywords: Airports -- Management.; elektronické knihy; electronic books